Sustained release formulations of citronella oil nanoemulsion using cavitational techniques - Agrawal N.; Maddikeri G.L.; Pandit A.B. (My University, 2025)
Nanoemulsion synthesis has proven to be an effective way for transportation of immobile, insoluble bioactive compounds. Citronella Oil (lemongrass oil), a natural plant extract, can be used as a mosquito repellent and has less harmful effects compared to its available market counterpart DEET (N, N-Diethyl-meta-toluamide). Nanoemulsion of citronella oil in water was prepared using cavitation-assisted techniques while investigating the effect of system parameters like HLB (Hydrophilic Lipophilic Balance), surfactant concentration, input energy density and mode of power input on emulsion quality. The present work also examines the effect of emulsification on release rate to understand the relationship between droplet size and the release rate. Minimum droplet size (60 nm) of the emulsion was obtained at HLB of 14, S/O S/O = Surfactant to oil weight ratio (g/g).1 ratio of 1.0, ultrasound amplitude of 50% and irradiation time of 5 min. This study revealed that hydrodynamic cavitation-assisted emulsification is more energy efficient compared to ultrasonic emulsification. It was also found that the release rate of nanoemulsion enhanced as the droplet size of emulsion reduced. © 2016 Elsevier B.V.